A multicentric prospective analysis of maxillofacial trauma in the elderly population. Issue 3 (12th February 2022) - Bojino, Alessandro; Roccia, Fabio; Carlaw, Kirsten; Aquilina, Peter; Rae, Euan; Laverick, Sean; Romeo, Irene; Iocca, Oreste; Copelli, Chiara; Sobrero, Federica; Segura‐Pallerès, Ignasi; Ganasouli, Dimitra; et al.
Abstract: Background/Aims: The growth of the global elderly population will lead to an increase in traumatic injuries in this group, including those affecting the maxillofacial area, with a heavier load on health systems. The aim of this multicentric prospective study was to understand and evaluate the incidences, causes and patterns of oral and maxillofacial injuries in patients aged over 60 years admitted to 14 maxillofacial surgical departments around the world. Methods: The following data were collected: gender, cause and mechanism of maxillofacial fracture, alcohol and drug abuse at the time of trauma, fracture site, Facial Injury Severity Scale score, associated injury, day of trauma, timing and type of treatment and length of hospitalization. Statistical analyses were performed using non‐parametric and association tests, as well as linear regression. Results: Between 30 September 2019 and 4 October 2020, 348 out of 2387 patients (14.6%), 197 men and 151 women (ratio 1.3:1; mean age 72.7 years), were hospitalized. The main causes of the maxillofacial fractures were falls (66.4%), followed by road traffic accidents (21.5%) and assaults (5.2%). Of the 472 maxillofacial fractures, 69.7% were in the middle third of the face, 28% in the lower third and 2.3% in the upper third. Patients with middle third fractures were on average 4.2 years older than patients with lower third fractures (95% CI 1.2–7.2). Statistical analysis showed that women were more involved in fall‐related trauma compared with males ( p  < .001). It was also shown that road traffic accidents cause more fractures in the lower third ( p  < .001) and in the middle third‐lower third complex compared with upper third ( p  < .001). Conclusions: Maxillofacial fractures in the elderly were more frequent in European and Australian centres and affected men slightly more than women. Falls were the leading cause of fractures, especially among women. The middle third of the face was most often affected, and conservative treatment was the most common choice for the management of such patients.